Pengaruh Saluran Pembelian dan Merek terhadap Keputusan Pembelian Jasa Pengiriman Barang PT Pos Indonesia - Sholehudin, Muhammad; Gunawan, Ce (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
The experience and extensive network of goods delivery service PT Pos Indonesia (Persero) does not make it the main choice for consumers. In fact, recently the goods delivery service PT Pos Indonesia (Persero) has always been inferior to its competitors from private companies. There are at least two top factors in choosing PT Pos Indonesia (Persero) goods delivery services by consumers, namely purchasing channel selection and brand selection. The purpose of this research is to determine the influence of purchasing channel selection and brand selection on purchasing decisions for PT Pos Indonesia (Persero) goods delivery services among e-commerce consumers. The research method used in this research is a quantitative research method using primary data obtained using a questionnaire distributed to 97 people and using secondary data as supporting data. The analytical methods used in this research are validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, hypothesis test using the f test, t test, and coefficient of determination test. The results of this research show that the choice of purchasing channel and brand choice influence partially or jointly the decision to purchase PT Pos Indonesia (Persero) goods delivery services among e-commerce consumers.